Factors Associated with Successful Mentoring of Parents Addressing Childhood Obesity: A Mixed Methods Approach - Gabriela Abigail Villanueva; Byron Alexander Foster (Hindawi Limited, 2016)
Objective. Parents mentoring other parents as a behavioral intervention for child obesity is novel with limited data describing the experience and dynamics of this approach. This study aimed to describe the experiences of parent mentors and the self-efficacy and attitudes of their mentees in the context of a clinical trial for childhood obesity. Methods. The context for this study was a randomized clinical trial using either parent mentors or a community health worker engaging parents of obese children in behavioral change over six months. Parent mentors were interviewed at the mid-point of the intervention using a semistructured questionnaire to elicit their perceptions and experiences during the process of mentoring. Parent mentees completed a survey assessing their self-efficacy, perception of the parent mentor, and attitudes and beliefs related to their child's weight. Results. The qualitative analysis of parent mentor interviews indicated high commitment despite their nonprofessional status, facing challenges of engagement with fellow parents and attitudes of persistence and being nonjudgmental. The parent mentee ratings of parent mentors were overall very high and similar to the ratings of a community health worker (paraprofessional). Conclusion. The data suggest that a parent mentor model of intervention for child obesity is an acceptable mode of approaching behavior change in the Hispanic population around childhood obesity with potential for scalability if proven effective.